2008
DOI: 10.1348/135532507x238682
|View full text |Cite
|
Sign up to set email alerts
|

The role of confirmation bias in suspect interviews: A systematic evaluation

Abstract: Purpose. The three studies presented in this paper systematically examined the effect of expectations of guilt on interviewer questioning style, confession, denial rates, and suspects' verbal behaviour during interview.Method. Undergraduate students were recruited to participate in the three studies. In Study 1, 61 participants formulated questions that they wanted to ask a suspect to determine whether or not they cheated on a task. Prior to formulating their questions, participants were led to believe that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(156 citation statements)
references
References 20 publications
2
144
0
10
Order By: Relevance
“…Several studies have examined ways to mitigate the negative effects of CB in similar investigation tasks (Hill, Memon, & McGeorge, 2008;Krems & Zierer, 1994;Oswald & Grosjean, 2004;Rassin, 2010). For example, O'Brien's (2009) study of CB in criminal investigations demonstrated that participants who considered why their hypothesis might be wrong showed less bias, whereas those who generated several additional hypotheses did not, suggesting that too many alternatives or too much high task complexity can hinder one's systematic processing ability.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Several studies have examined ways to mitigate the negative effects of CB in similar investigation tasks (Hill, Memon, & McGeorge, 2008;Krems & Zierer, 1994;Oswald & Grosjean, 2004;Rassin, 2010). For example, O'Brien's (2009) study of CB in criminal investigations demonstrated that participants who considered why their hypothesis might be wrong showed less bias, whereas those who generated several additional hypotheses did not, suggesting that too many alternatives or too much high task complexity can hinder one's systematic processing ability.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Most recently, Hill, Memon, & McGeorge (2008) find similar results in their study of interrogation -that independence of actual guilt, interrogators with a hypothesis of guilt frame questions the answers to which seem more corroborative of guilt. See also Kassin, Goldstein, & Savitsky (2003) ;Meissner, & Kassin (2004).…”
Section: B the Behavior Of Policementioning
confidence: 63%
“…Through a review of existing literatures, we find that there are two main research directions: One is cognitive bias when using connectionism strategy, it is found that this strategy can cause three kinds of effects, the first is confirmation bias in the procedure of searching for cues, it tends to continue to search for cues which support the dominant scheme and ignore the cues that do not support the dominant scheme, this effect often occurs in the field of judicial trials and leads to a wrong judgment [8]. The second is coherence shift during the process of cue evaluation, namely policymakers often overestimate the importance of cues which support the dominant scheme while underestimate the importance of cues that don't support the dominant scheme.…”
Section: Literature Reviewmentioning
confidence: 99%